DIPLOMATIC POWER WEAVING OF GLOBAL SYSTEMIC CHANGE: THE EUROPEAN UNION’S STEPS - Stefanović-Štambuk, Jelica (Serbian political thought, 2024)
This research seeks to provide a viable understanding of the main specificities of incongruences of reality with the theoretical assumptions on the working of the international by developing the concept of diplomatic power. The relational theoretical perspective on diplomacy as the peaceful search for the consent on just and commonised sharing of life, time, and planet affords the conceptualisation of diplomatic power as the non-episodic offering to others what they need, when, how, and for as long as they need it free from conditions and expectations of returns. The inquiry focuses on how diplomatic power is weaving out of several relational threads of relationships, the one of mutuality transcending the hegemonic “complex interdependence”. In this futuring process, the unfolding of diplomacy transforms the global relations system, prefigurating its emergent participatory democratic structures. The People’s Republic of China mobilised offerings to others of what they need conditionality free or non-rewarding for their conduct favourable to its interests have been the challenge to the European Union and the United States of America. Comparing their efforts, backed by the Group of 7, to counter China’s diplomatic power has proved impotent even when they combined their diplomatic power. Yet, the enlarged supply of options empowers long-marginalized states. The conflictual dynamics driven by the European Union and the United States of America competing with the People’s Republic of China is undermining the possibility of mutuality as a new relational pattern to order the world safe for just humanity on a secure planet.
Keywords: diplomacy; relational theory; diplomatic power; will for relationships; mutuality; Evropska unija; China; United States of America; Ordedemonium